2011
DOI: 10.1007/s12663-011-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Botox as an Adjunct to Orthognathic Surgery For A Case of Severe Vertical Maxillary Excess

Abstract: Large skeletal discrepancies are sometimes only minimised but not eliminated by orthognathic surgeries. Administration of Botox has been advocated as an effective minimally invasive procedure to tackle aesthetic compromises like gummy smile and the like. This article elaborates on the surgical management of a case of severe vertical maxillary excess with Botox as an adjunct therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
23

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 13 publications
0
32
0
23
Order By: Relevance
“…Many have studied the components of an attractive smile; most studies concluded that the perfect amount of maxillary gingival tissue shown during smiling is 3 mm. 4 Gummy smile, or excessive gingival display in the maxillary arch on smiling, is known as the difference between the lower margin of the upper lip and the superior margin of the incisors 1,4,5 and is considered one of the…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many have studied the components of an attractive smile; most studies concluded that the perfect amount of maxillary gingival tissue shown during smiling is 3 mm. 4 Gummy smile, or excessive gingival display in the maxillary arch on smiling, is known as the difference between the lower margin of the upper lip and the superior margin of the incisors 1,4,5 and is considered one of the…”
Section: Introductionmentioning
confidence: 99%
“…5 Over time, different solutions were proposed to treat this disorder that ranged from complicated to simple. Orthognathic surgeries, such as LeFort I osteotomy and bone resection, orthodontic treatment by incisor intrusion, crown lengthening, gingivoplasty, and botulinum toxin (Botox) injections are all different methods of treating a gummy smile depending on the patient's situation.…”
mentioning
confidence: 99%
See 3 more Smart Citations